IMPLEMENTASI TATA KELOLA SUMBER DAYA MANUSIA DALAM PENGATURAN OPERASIONAL BANDAR UDARA - Sunarno Sunarno (Approach : Jurnal Teknologi Penerbangan, 2019)
The aviation industry certainly cannot be separated from airports, which are the most important links between the islands of Indonesia and between other countries from all over the world. Everyone involved with airport operations must know, understand and master the important parts of an airport. This research uses qualitative research, primary data is collected through documentation and analyzed using an interactive analysis model. In connection with the needs of the aviation industry, PPI graduates in 2019 succeeded in "Go International" at the ICAO Qatar Developing Countries Scholarship in the field of Air Traffic Controllers, the key is to improve skills, professionals in the disciplinary corridors of the PPI Curug. An important step is to improve the human resource capacity of cadets. "Capacity Building" is the development of skills and capabilities, such as leadership, management, and others. This implementation can realize "Good Corporate Governance" and contribute to 3S + 1C, namely "Safety, Security, Services and Compliance". The implementation of airport governance supported by Capacity Building is very significant and effective in various situations and conditions such as the Covid-19 pandemic. Also capable of adapting to various forms of changes that correlate with airport operational arrangements.